Criteria for the selection of the typical team: Case of U17 footballers - Blidi, Touati; Mokkedes, Moulay Idriss; Zerf, Mohammed; Bengoua, Ali (Journal of Sport Science Technology and Physical Activities, 2018)
Depending on the literature, where aerobic energy system is highly taxed during a football game, with average and peak heart rates around 85% and 98% of maximal values, respectively, corresponding to an average oxygen uptake of around 70% of maximum, as an important, factor in selecting the players at a top-class level. Our aims in the present study look forward to examine the effectiveness of the methods used by the Algerian coach to select the team type (11 entries). To archive this goal, we use the descriptive method, by testing 24 confirmed players from the team Esperance of Mostaganem under 17 yr in anthropometric parameters (BMI, BFP ) and test BRIKCI to calculate them VO2max, seen our objectives are to clarified the actual question: On what criteria our U17 coaches select their football teams. Our data test and statistical practice confirms the failure of the traditional methods practiced by our coaches, relying on their experience, confirmed by the Algerian similar introduce in this paper. Since that, we instructed to our coaches the scientific method based on batteries test established by our scientists in this field.